Temporal evolution and functional outcome of no reflow: sustained and spontaneously reversible patterns following successful coronary recanalisation. Issue 7 (1st July 2003) - Galiuto, L; Lombardo, A; Maseri, A; Santoro, L; Porto, I; Cianflone, D; Rebuzzi, A G; Crea, F
Abstract : Objective: To identify in humans the temporal patterns of no reflow and their functional implications. Methods: 24 patients with first acute myocardial infarction and successful coronary recanalisation by recombinant tissue-type plasminogen activator (n = 15) or primary percutaneous transluminal coronary angioplasty (n = 9) were studied by myocardial contrast echocardiography within 24 hours of recanalisation and at one month's follow up. Myocardial contrast echocardiography was performed by intermittent harmonic power Doppler and intravenous Levovist. The regional contrast score index (CSI) was calculated within dysfunctioning myocardium. Videointensity was measured (dB) within risk and control areas and their ratio was calculated. Results: In 8 patients reflow was observed at 24 hours and persisted at one month. Conversely in 16 patients areas of no reflow were detectable at 24 hours. At one month, no reflow was spontaneously reversible in 9 patients (mean (SD) CSI and videointensity ratio improved from 2.5 (0.5) to 1.4 (0.6) and from 0.6 (0.1) to 0.7 (0.1), respectively; p < 0.05) and was sustained in the remaining 7 patients (CSI and videointensity ratio remained unchanged from 2.6 (0.6) to 2.6 (0.5) and from 0.5 (0.2) to 0.5 (0.2), respectively; NS). Left ventricular function improved significantly in patients with reflow and reversible no reflow. Volumes were enlarged only in patients with sustained no reflow. Conclusions: No reflow detected at 24 hours may be sustained or spontaneously reversible at one month. Such reversibility of the phenomenon is associated with preserved left ventricular volumes and function. Clarification of the mechanisms of delayed reversibility may lead to tailored treatment of no reflow even in the subacute phase of myocardial infarction.